Anxiety, depression, perceived social support and quality of life in Malaysian breast cancer patients: a 1-year prospective study - Ng, Chong Guan; Mohamed, Salina; See, Mee Hoong; Harun, Faizah; Dahlui, Maznah; Sulaiman, Ahmad Hatim; Zainal, Nor Zuraida; Taib, Nur Aishah (Health and quality of life outcomes, 2015)
Depression and anxiety are common psychiatric morbidity among breast cancer patient. There is a lack of study examining the correlation between depression, anxiety and quality of life (QoL) with perceived social support (PSS) among breast cancer patients. This study aims to study the level of depression, anxiety, QoL and PSS among Malaysian breast cancer women over a period of 12 months and their associations at baseline, 6 and 12 months. It is a 12 months prospective cohort study. Two hundred and twenty one female patients were included in the study. They were assessed at the time of diagnosis, 6 months and 12 month using Hospital Anxiety and Depression Scale (HADS), Quality-of-Life Questionnaire (QLQ-C30), Version 3.0 of the EORTC Study Group and Multidimensional Scale of Perceived Social Support (MSPSS). The information of age, ethnicity, types of treatment, and staging of cancer were collected. The HADS anxiety and depression subscales scores of the subjects were relatively low. The level of anxiety reduced significantly at 6 and 12 months (Baseline - 6 months, p = 0.002; Baseline - 12 months, p < 0.001). There were no changes in the level of depression over the study period. The global status of QoL and MSPSS scores were relatively high. Correlation between the global status of QoL and MSPSS for the study subjects was positive (Spearman's rho = 0.31-0.36). Global status of QoL and MSPSS scores were negatively correlated with anxiety and depression. Malaysian breast cancer women had relatively better QoL with lower level of anxiety and depression. Perceived social support was an important factor for better QoL and low level of psychological distress. It reflects the importance of attention on activities that enhance and maintain the social support system for breast cancer patients.